Experimental research of ICP reactor for plasma-chemical etching - Dudin, S.V.; Zykov, A.V.; Dahov, A.N.; Farenik, V.I. (Вопросы атомной науки и техники, 2006)
The results of systematic experimental researches of plasma-chemical etching reactor in the inductive mode are presented in this paper. Measurements of the integral discharge parameters (inductor voltage, gas pressure, input power) have been carried out as well as probe measurements of spatial distribution of local plasma parameters (plasma density, temperature and electron energy distribution function) and radial profiles of ion current to processed surface. The measured dependences differ essentially for atomic (Ar) and molecular (O₂,N₂,CF₄) gases. As the range of working pressure covers diffusive and collisionless modes of charged particles movement, radial distribution of ion current density and its absolute value change significantly. Comparison of the obtained results with the calculations executed using “Global” spatially averaged model and 2D-fluid model is carried out.